2017
DOI: 10.1007/s00264-017-3572-5
|View full text |Cite
|
Sign up to set email alerts
|

Femoro-acetabular impingement: anatomic study of reliability and accuracy of alpha angle and offset ratio on fifty consecutive peri-operatively resected femoral heads

Abstract: AA on axial X-ray view reflected the real AA in our series, but the risk of cartilage damage cannot be predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Since the definition was proposed, a large number of scholars have conducted research on it from many directions and have made certain progress and have further in-depth understanding of the disease. According to the different manifestations of imaging, the disease is divided into three types: cam type (CAM-type), clamp type (PINCER-type), and mixed type (MIX type); it is believed that the disease should be diagnosed at an early stage and related treatment [10,11]. However, with a large number of clinical observations, it has been found that the x-ray signs of the so-called FAI also have a large number of manifestations in people without any hip symptoms; a study by Laborie et al found that about half of adults without hip symptoms have at least one or more FAIrelated symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Since the definition was proposed, a large number of scholars have conducted research on it from many directions and have made certain progress and have further in-depth understanding of the disease. According to the different manifestations of imaging, the disease is divided into three types: cam type (CAM-type), clamp type (PINCER-type), and mixed type (MIX type); it is believed that the disease should be diagnosed at an early stage and related treatment [10,11]. However, with a large number of clinical observations, it has been found that the x-ray signs of the so-called FAI also have a large number of manifestations in people without any hip symptoms; a study by Laborie et al found that about half of adults without hip symptoms have at least one or more FAIrelated symptoms.…”
Section: Introductionmentioning
confidence: 99%